THE ROLE OF DIGITAL TECHNOLOGIES IN ENHANCING CREATIVE THINKING AND AESTHETIC COMPETENCE IN ART EDUCATION - Toshmuhammedova Iroda Alibek qizi (ILMIY YANGILIKLAR VA INTELLEKTUAL TADQIQOTLAR, 2025)
Abstract: This article examines the theoretical and practical aspects of using digital technologies to enhance students’ and teachers’ creative thinking and aesthetic competence in art education. Digital tools, interactive methods, and multimedia resources foster creative problem-solving, visual communication skills, and pedagogical effectiveness. The article analyzes the pedagogical importance of innovative technologies in art lessons, methods for developing creative thinking and aesthetic competence, and practical recommendations for teachers and students. Integration of digital tools into art education is shown to improve creative processes, support independent learning, and develop professional competencies.